Opticlock: Transportable and easy-to-operate optical single-ion clock. (December 2021) - Stuhler, J.; Abdel Hafiz, M.; Arar, B.; Bawamia, A.; Bergner, K.; Biethahn, M.; Brakhane, S.; Didier, A.; Fortágh, J.; Halder, M.; Holzwarth, R.; Huntemann, N.; et al.
Abstract: We report on a transportable and easy-to-operate optical clock utilizing the 2 S1/2 - 2 D3/2 transition of a single trapped 171 Yb + ion at 436 nm. Developed within a pilot project for quantum technology in Germany lead by industry, the clock is set up in two 19″ racks. In this way, transportation can easily be realized, and the large degree of automatization allows for operation outside highly specialized laboratories for applications beyond basic research. Comparisons to existing high-accuracy optical clock systems enable a verification of the clock's stability and uncertainty budget at the low 10 −17 level. During these tests, operation with 99.8% availability over more than 14 days has been achieved.